الممارسات الاخلاقية والمسؤولية الاجتماعية لأعمال السياحة - رياض, خوازم; الصغير, خرخش (University of eloued جامعة الوادي, 2021)
"في ختام دراستنا المتعلقة بالممارسات الاخلاقية والمسؤولية الاجتماعية لأعمال السياحة توصلنا إلى أن الممارسات المهنية من أهم العوامل التي تؤدي الى تطوير مهارات العاملين ويعكس ذلك الاهتمام الذي يوليه الموظف لمهنته، حيث أن عدم وجود أثر الالتزام سوف يؤثر بشكل مباشر على سمعة المنظمة. ولقد خلصنا في هذه الدراسة وعلى ضوء هذه المعطيات والأرقام إلى بعض النتائج كإجابة على فرضيات الدراسة أهمها: أن استهداف الزبائن أكثر من حيث الممارسات الاخلاقية والمسؤولية الاجتماعية لأعمال المنطقة السياحية. أن فئة الذكور أكثر استهداف من الاناث في السياحة ككل وفي الممارسات الاخلاقية والمسؤولية الاجتماعية للسياحة ومهتمون بمجال السياحة أكثر من الاناث أن من لديهم شهادات مستهدفين أكثر في السياحة والممارسات الاخلاقية والمسؤولية الاجتماعية للسياحة أما بدون شهادة ضئيلة مقارنة بهم لانهم مقبلون على السياحة أكثر أن أكبر فئة معينة نظرا لمجال خبرتهم الطويل ومع نفس الوقت لاكتساب المزيد من الخبرات وتجسيد دورهم في الممارسات الاخلاقية والمسؤولية الاجتماعية لأعمال السياحة. ""At the conclusion of our study related to the ethical practices and social responsibility of tourism business, we concluded that professional practices are one of the most important factors that lead to the development of workers’ skills, and this reflects the interest that the employee gives to his profession, as the absence of the impact of commitment will directly affect the reputation of the organization. In this study, and in light of these data and figures, we have concluded some results as an answer to the study’s hypotheses, the most important of which are: To target customers more in terms of ethical practices and social responsibility for the business of the tourist area. The male category is more targeted than females in tourism as a whole and in the ethical practices and social responsibility of tourism, and they are more interested in the field of tourism than females Those who have certificates are targeted more in tourism, ethical practices and social responsibility for tourism, but without a certificate, they are insignificant compared to them because they are more likely to tourism That the largest specific category due to their long field of experience and at the same time to gain more experience and embody their role in ethical practices and social responsibility of tourism business. "
ماستر تسويق
Keywords: الممارسات الاخلاقية، المسؤولية الاجتماعية، أعمال السياحة.; Ethical practices, Eocial responsibility, Tourism business.